Women in Animal Husbandry: Examining Socioeconomic, Communication, Psychological Characteristics and Constraints to Decision-Making - Pandey, Ankita; Rai, D. P. (International Journal of Bio-resource and Stress Management, 2024)
This research was conducted in the Department of Technology Transfer, Faculty of Agriculture, MGCGVV, Chitrakoot, Satna, Madhya Pradesh, India during 2022 to investigate the constraints faced by rural farm women while participating in decision-making processes related to animal husbandry activities. A sample of 340 farm women was surveyed in Dewas district of Madhya Pradesh, India in year 2019–20. Socioeconomics distribution reveals that the majority of respondents were in the medium age category (36 to 55 years), comprising 56.47% of the sample. The education status of participants varied, with a large proportion (43.23%) being illiterate. Among the educated individuals, primary education was the most common (36.17%), followed by middle education (12.94%). Regarding annual income, the majority fell into the medium category (56.76%), with low and high-income groups comprising 22.06% and 21.18% respectively. In terms of milch animals, the medium category (5–10 animals) was the most prevalent (45.88%). The study reveals that costly management, lack of technical knowledge, high cost of milch animals, social and cultural norms, and dominancy of other family members are significant barriers to women’s participation. The top three constraints identified by the women were costly management (97.35%), lack of technical know-how (96.76%), and high cost of milch animals (87.05%). These constraints highlight the need for providing technical and financial assistance to women engaged in animal husbandry activities. The findings underscore the importance of addressing these constraints through technical and financial assistance, capacity building programs, and improvements in veterinary services. By overcoming these constraints, women’s participation in decision-making processes can be enhanced, leading to improved agricultural practices and livelihoods in rural areas.